“ To describe the cooperative learning influence as a teaching strategy to improve the speaking skill in english language at 3er año del bachillerato general unificado at Unidad Educativa "Eloy Alfaro" of Santo Domingo de los Tsachilas province during the academic period 2015-2016” - Quishpe Maigua, Karla Janneth (2016)
stimulates the relationship between teachers and students so that a meaningful learning and learning environment can be established. The purpose of this method is to achieve common goals together. The objective of this method is to identify how the teacher uses cooperative learning in the classroom and how it helps students to develop their speaking skills. This investigation was done with students at Unidad Educativa “Eloy Alfaro” in the province of Santo Domingo de los Tsáchilas, during the academic term May – September 2016. This study consists of researching parameters that permit an easy understanding of the problem. It focuses on a qualitative aspect using ethnography methodology with a documental investigation; using observation guide as an instrument, after observing and collecting data on different classes, the results are analyzed and investigated, so that they are easier to understand. The results reflected that, when the students work in groups, only one or two students actually do the activity; there is not any interaction among the members of the group to complete the assigned task; the students do not have interest on developing their learning circle; also, the teacher does not use other kinds of strategies of forming work groups than “afinity”; therefore, it is possible to state that the teacher wrongly applies Cooperative Learning Method in class.